2015
DOI: 10.5811/westjem.2015.6.25752
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Aortic Dissection in Emergency Department Patients is Rare

Abstract: IntroductionAortic dissection is a rare event. While the most frequent symptom is chest pain, that is a common emergency department (ED) chief complaint and other diseases causing chest pain occur much more often. Furthermore, 20% of dissections are without chest pain and 6% are painless. For these reasons, diagnosing dissections may be challenging. Our goal was to determine the number of total ED and atraumatic chest pain patients for every aortic dissection diagnosed by emergency physicians.MethodsDesign: Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 13 publications
1
43
0
1
Order By: Relevance
“…Adult patients for potential inclusion were identifi ed within our electronic medical record system using the International Classification of Diseases, 9th version (ICD-9) and coding for aortic diseases at 441.XX. [14] Patients who were transferred directly from another emergency department (ED) to our academic medical center for management of acute aortic dissections were included. Patients who initially presented to our academic medical center and those who were not a direct transfer from a referring ED were excluded.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult patients for potential inclusion were identifi ed within our electronic medical record system using the International Classification of Diseases, 9th version (ICD-9) and coding for aortic diseases at 441.XX. [14] Patients who were transferred directly from another emergency department (ED) to our academic medical center for management of acute aortic dissections were included. Patients who initially presented to our academic medical center and those who were not a direct transfer from a referring ED were excluded.…”
Section: Patient Selectionmentioning
confidence: 99%
“…. Mean patient age was 61(14) years; median length of stay in the ED was 300 [205-415] minutes; mean triage SBP and HR were 150 (42) mmHg and 78(19) beats/minute, respectively; mean SBP and HR at referring ED departure were 139 (31) mmHg and 77(16) beats/minute, respectively.Among 287 ED clinical records analyzed, 105 (36.6%) contained adequate documentation of clinical care. However, 182 (63.4%) ED clinical records were…”
mentioning
confidence: 99%
“…The reported incidence of AD varies in the available literature but is thought to be 3.5 per 100 000 cases . One study reported an ED incidence of 1 in 12, 200 patients per year from a database of 9.5 million ED patients …”
Section: Conditionmentioning
confidence: 99%
“…2 One study reported an ED incidence of 1 in 12, 200 patients per year from a database of 9.5 million ED patients. 3 Timely diagnosis is crucial. Without treatment, Type A dissection is reported to have a cumulative mortality of 1-2% per hour, rising to an 80% mortality within 2 weeks.…”
Section: Conditionmentioning
confidence: 99%
“…However, its diagnosis is challenging given heterogeneous symptoms and a low incidence estimated at 2.6–6 cases per 100,000 person-years [ 1 3 ]. Although 8–10% of all patients admitted to a general emergency care department present with acute chest pain, only one in 980 of these patients will have an acute aortic dissection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%